PENGENALAN SEJAK DINI PROFESI APOTEKER MELALUI METODE STORYTELLING BERMUATAN PENDIDIKAN KARAKTER - Rina Wijayanti (LPPM Universitas Putera Batam, 2019)
Early childhood (2-6 years) is a golden age as well as an appropriate time to start character education and learn various skills that are useful for children as a foundation for higher skills in the future. The application of character education at that age will continue to imprint and underpin good character values that are beneficial to the child's future. TK Senyiur Indah is one of the educational institutions implementing character education through the implementation of the 2013 Curriculum. One of the themes raised in character education at TK Senyiur Indah is Work or Profession. However, the introduction of the health profession that was delivered at the time of learning activities at the Beautiful Senyiur Kindergarten was only limited to the profession of doctors and nurses. Students have not been introduced to the pharmacist profession. Whereas in fact, the pharmacist profession plays an important role in the success of health programs. The purpose of this service is to increase students' knowledge about the pharmacist profession through storytelling activities containing character education as an effort to improve health. The method used in this community service activity is the early introduction of the pharmacist profession, using the storytelling method using visual aids such as finger puppets, as well as games about the process of making drugs in the form of capsules. Solution to the agreement with partners can be seen through indicators of the success of this activity as measured by increasing the acquisition of pretest and posttest scores, which shows an increase in students' knowledge. The conclusion in this activity is the high enthusiasm of students so as to increase knowledge, skills, students in terms of medicine and the pharmacist profession so as to improve students' health.